COMPARISON OF CONTINUATION OF POST-PLACENTAL INSERTION OF COPPER T AFTER CESAREAN SECTION AND NORMAL VAGINAL DELIVERY - Khajotia, Santosh; Shakeel, Mohd; Kochar, Swati; Bano, Tanu (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to assess the efficacy of post-placental copper T insertion following vaginal and cesarean delivery. Methods: This is a prospective study conducted for the period of 1 year on pregnant females undergoing deliveries at Department of Obstetrics and Gynecology, Sardar Patel Medical College and AGH, Bikaner. The total number of postpartum intrauterine contraceptive device inserted participants included in the study were 200, divided into two groups vaginal (group A) and lower segment cesarean section (LSCS) (group B) groups. Results: Mean age of the patients was 26.15±4.02 years. Most of the acceptors in both the groups were para-2 with 30% in vaginal group and 76% in LSCS group. The complaints at 6 weeks follow-up, in both groups, were similar, but the rate of removal was higher in vaginal group (9%) compared to LSCS group (2%). At 3 months follow-up, in vaginal group, the most common complaint was bleeding per vagina (PV) in 7.31% cases whereas missing thread 31.25% in LSCS group. Over a period of 3 months, the main reason for intrauterine contraceptive devices (IUCD) removal was bleeding PV in both group (six cases in vaginal group and three cases in LSCS group). Conclusion: Immediate post-partum insertion of IUCD appears to be safe and effective method of contraception.